THE REGENERATION OF THE BLOOD - Hall, Winfield S. (The Rockefeller University Press, 1896)
a. The blood of apparently normal animals undergoes considerable variations within physiological limits. b. After a loss of blood the regeneration is more rapid if there has been a transfusion of an artificial serum. c. Regeneration after transfusion is less rapid during the first half of the regeneration period than during the second half. d. The regenerative processes once stimulated into activity carry the blood, qualitatively, considerably beyond the established normal. (See Plate XXXIII.) Otto (2) observed a similar phenomenon. e. The quantity of hæmoglobin per volume of red blood-corpuscles is not constant. f. The volume of red blood-corpuscles varies as the product of the average volume of individual corpuscles and the number of corpuscles per unit volume. (V ∝ v x n). g. When the number of the corpuscles increases the size decreases, and conversely, (n ∝½). h. The quantity of hæmoglobin varies in general with the number of red blood-corpuscles per unit volume. (Hb. ∝ n).